Arsenic and cadmium induced macronutrient deficiencies trigger contrasting gene expression changes in rice. (1st May 2022) - Raghuvanshi, Rishiraj; Raut, Vaibhavi V.; Pandey, Manish; Jeyakumar, Subbiah; Verulkar, Satish; Suprasanna, Penna; Srivastava, Ashish Kumar
Abstract: Arsenic (As) and cadmium (Cd), two major carcinogenic heavy metals, enters into human food chain by the consumption of rice or rice-based food products. Both As and Cd disturb plant-nutrient homeostasis and hence, reduces plant growth and crop productivity. In the present study, As/Cd modulated responses were studied in non-basmati (IR-64) and basmati (PB-1) rice varieties, at physiological, biochemical and transcriptional levels. At the seedling stage, PB-1 was found more sensitive than IR-64, in terms of root biomass; however, their shoot phenotype was comparable under As and Cd stress conditions. The ionomic data revealed significant nutrient deficiencies in As/Cd treated-roots. The principal component analysis identified NH4 + as As-associated key macronutrient; while, NH4 + /NO3 − and K + was majorly associated with Cd mediated response, in both IR-64 and PB-1. Using a panel of 21 transporter gene expression, the extent of nutritional deficiency was ranked in the order of PB-1(As)<IR-64(As)<PB-1(Cd)<IR-64(Cd). A feed-forward model is proposed to explain nutrient deficiency induced de-regulation of gene expression, as observed under Cd-treated IR-64 plants, which was also validated at the level of sulphur metabolism related enzymes. Using urea supplementation, as nitrogen-fertilizer, significant mitigation was observed under As stress, as indicated by 1.018- and 0.794-fold increase in shoot biomass in IR-64 and PB-1, respectively compared to that of control. However, no significant amelioration was observed in response to supplementation of urea under Cd or potassium under As/Cd stress conditions. Thus, the study pinpointed the relative significance of various macronutrients in regulating As- and Cd-tolerance and will help in designing suitable strategies for mitigating As and/or Cd stress conditions.